Peningkatan Kualitas Mutu Kemasan Permen Olahan Rumput Laut Masyarakat Kepulauan Seribu Melalui Peningkatan Estetika - Silvia, Deli; Imam, Saeful; yeti, Muryeti; Prastiwinarti, Wiwi; Ningtyas, Rina; nain, Zulkar; Purnama Sari, Novi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2022)
One of the potential products of the Pulau Seribu as a marine destination in the north of Jakarta is its seaweed products, with the best quality and the mainstay of seaweed exports in Indonesia. Basically, not a few of the MSMEs in the Pulau Seribu already have production permits, business permits, and market seaweed products, but there are still some who experience problems in using their product packaging. As a result, the product is more difficult to market and has a low selling value. To overcome the problems faced by MSMEs, the Technology Industry of Prining Packaging Department (TICK) in collaboration with partners (Pondok Cafe and Karang Taruna) carries out community service activities with the aim of: making packaging based on products, materials, designs, and packaging forms that are efficient and can be applied. by MSMEs. The science and technology program for the community is in the form of helping MSMEs in the Pulau Seribu through partners and youth organizations in the Pulau Pramuka area to make packaging independently. The method for conducting this science and technology program for the community is: through training and mentoring. Among the stages are conducting a preliminary survey of partners (MSMEs), designing packaging designs, making packaging according to the needs of MSMEs and training and assistance in packaging production. The output of this activity is the availability of primary packaging for candies’s seaweed products, driving the community's economy and increasing sales of partner products.